Pneumatosis Intestinalis and Concurrent Focal Diaphragmatic Pneumatosis Cystoides Presenting With Pneumoperitoneum in a 20 Year‐Old Male: A Case Report - Manal Fasih; Patricia Colucci; Kara Monday (Clinical Case Reports)
ABSTRACT Pneumatosis cystoides intestinalis can present with concurrent diaphragmatic cysts, a previously undocumented phenomenon. Surgical management may be required, but further investigation is needed to understand the pathogenesis and optimize management in atypical and chronic cases, such as this case with a history of corrected intestinal malrotation.